Pengaruh Pemahaman Keagamaan dan Literasi Media terhadap Penyebaran Hoax di Kalangan Mahasiswa - Aliasan Aliasan (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2017)
The understanding of religion and media literacy is becoming very important nowadays. The pattern is both textual and contextual which means it should be comprehensive and go in line with the norms lead to the kindness to all the people. The bombing of information need the literacy skill to filter the information. This field research aims to know the influence of the religious understanding and media literacy to the spread of hoax to the students. Data used is quantitative and the result shows that variable X1 (Religious understanding) has 5 dimensions, they are ideology, ritualistic, consequence, experiential, and intellectual. Variable X2 (media literacy) has 4 dimensions, they are Cognitive, Emotional, Aesthetic, and Moral. While, variable Y (the spread of hoax to the students) has 3 dimensions, they are hoax information, hoax source and hoax spreading pattern. The result shows that there are siginificant influence between the religious understanding and media lioteracy to the spread of hoax to the students.